Factor XIII Deficiency and Intracranial Hemorrhage - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
A 38 month old boy with excessive bleeding following circumcision as a newborn and two episodes of intracranial hemorrhage at four months and at 85 months of age is reported from the Scott and White Clinic, Temple, TX.